Hamstring Tendon Regeneration After Harvesting: A Systematic Review. (October 2015) - Suijkerbuijk, Mathijs A.M.; Reijman, Max; Lodewijks, Susanne J.M.; Punt, Jorien; Meuffels, Duncan E.
Background: Hamstring tendons are often used as autografts for anterior cruciate ligament (ACL) reconstruction. However, no systematic review has been performed describing consequences such as hamstring tendon regeneration rate and determinants of hamstring tendon regeneration. Purpose: To summarize the current literature regarding hamstring tendon rate regeneration, the time course of regeneration, and determinants of hamstring regeneration. Study design: Systematic review. Methods: A search was performed in the Embase, Medline (OvidSP), Web of Science, Cochrane, PubMed, and Google Scholar databases up to June 2014 to identify relevant articles. A study was eligible if it met the following inclusion criteria: tendons were harvested, regeneration at harvest site was assessed, population size was at least 10 human subjects, full-text article was available, and the study design was either a randomized controlled trial, prospective cohort study, retrospective cohort study, or case control study. A risk of bias assessment of the eligible articles was determined. Data describing hamstring tendon regeneration rates were pooled per time period. Results: A total of 18 publications met the inclusion criteria. The mean regeneration rate for the semitendinosus and gracilis tendons was, in all cases, 70% or higher. More than 1 year after harvesting, 79% (median [IQR], 80 [75.5-90]) of the semitendinosus tendons and 72% (median [IQR], 80 [61-88.5]) of the gracilis tendons were regenerated. No significant differences in regeneration rate could be found considering patient sex, age, height, weight, or duration of immobilization. Results did not clearly show whether absence of regeneration disadvantages the subsequent hamstring function. Five studies measured the regeneration rate at different moments in time. Conclusion: Hamstring tendons regenerated in the majority of patients after ACL reconstruction. The majority of the hamstring tendon regeneration was found to occur between 1 month and 1 year after harvest. No significant determinants for hamstring tendon regeneration could be identified because of a lack of research. The function and strength of the regenerated hamstring remained unclear.